2015
DOI: 10.1038/ng.3339
|View full text |Cite
|
Sign up to set email alerts
|

GmHs1-1, encoding a calcineurin-like protein, controls hard-seededness in soybean

Abstract: Loss of seed-coat impermeability was essential in the domestication of many leguminous crops to promote the production of their highly nutritious seeds. Here we show that seed-coat impermeability in wild soybean is controlled by a single gene, GmHs1-1, which encodes a calcineurin-like metallophosphoesterase transmembrane protein. GmHs1-1 is primarily expressed in the Malpighian layer of the seed coat and is associated with calcium content. The transition from impermeability to permeability in domesticated soyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
138
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(140 citation statements)
references
References 41 publications
2
138
0
Order By: Relevance
“…For example, cultivated soybeans show different degrees of seed coat permeability that are controlled by quantitative trait loci (17,18). Recently, a quantitative trait locus encoding calcineurin-like protein, GmHs1-1, was isolated by map-based cloning and reported to contribute to hardseededness in soybean with unknown mechanism (20). At the same time, an endo-1,4-β-glucanase gene, qHS1, was cloned by fine mapping and reported to be responsible for the formation of minute cracks by changing cell wall structure (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cultivated soybeans show different degrees of seed coat permeability that are controlled by quantitative trait loci (17,18). Recently, a quantitative trait locus encoding calcineurin-like protein, GmHs1-1, was isolated by map-based cloning and reported to contribute to hardseededness in soybean with unknown mechanism (20). At the same time, an endo-1,4-β-glucanase gene, qHS1, was cloned by fine mapping and reported to be responsible for the formation of minute cracks by changing cell wall structure (19).…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, seed hardness has been identified as a quantitative trait in soybean (17,18). With quantitative trait locus marker analysis, two single nucleotide polymorphism alleles were found to be associated with a seed coat permeability trait in various soybean cultivars (19,20). The mechanisms that change seed coat properties remain unknown.…”
mentioning
confidence: 99%
“…SCP (%) was recorded as percent of seeds imbibed water in respective tests (Kebede et al, 2014). As per Sun et al, (2015), the genotypes with SCP < 20% were categorized as hard-seeded and genotypes with SCP > 80% were grouped as soft-seeded. Data were analyzed for ANOVA, MSD, correlation coefficient using SAS software package version 9.4.…”
Section: Plant Materialsmentioning
confidence: 99%
“…A moderate level of seed coat impermeability or hard-seededness is important for the stored soybean seeds as it is desirable for their quality and viability in the tropics, where seeds lose viability within a short period of time after being harvested (Potts et al, 1978). Several studies have identified a common QTL underlying hard-seededness to an overlapping region on soybean Gm02 (Keim et al, 1990b; Watanabe et al, 2004; Liu et al, 2007; Zhang et al, 2008), which has been further confirmed by Sun et al (2015) and designated as (GmHs1-1) . Sun et al (2015) could delimit this QTL to a 22-kb region which contained only two genes, Glyma02g43700.1 and Glyma02g43710.1 .…”
Section: Qtlomics: Qtls To Genes In Soybeanmentioning
confidence: 82%
“…Several studies have identified a common QTL underlying hard-seededness to an overlapping region on soybean Gm02 (Keim et al, 1990b; Watanabe et al, 2004; Liu et al, 2007; Zhang et al, 2008), which has been further confirmed by Sun et al (2015) and designated as (GmHs1-1) . Sun et al (2015) could delimit this QTL to a 22-kb region which contained only two genes, Glyma02g43700.1 and Glyma02g43710.1 . Sequence characterization of these two genes identified a single SNP (C>T) in 8th exon of Glyma02g43700.1 which was responsible for the change of threonine amino acid to methionine.…”
Section: Qtlomics: Qtls To Genes In Soybeanmentioning
confidence: 82%